Endemicity of the cosmopolitan mesophilic chemolithoautotroph Sulfurimonas at deep-sea hydrothermal vents - Mino, Sayaka (ISME J, 2017)
Rich animal and microbial communities have been found at deep-sea hydrothermal vents. Although the biogeography of vent macrofauna is well understood, the corresponding knowledge about vent microbial biogeography is lacking. Here, we apply the multilocus sequence analysis (MLSA) to assess the genetic variation of 109 Sulfurimonas strains with ⩾98% 16S rRNA gene sequence similarity, which were isolated from four different geographical regions (Okinawa Trough (OT), Mariana Volcanic Arc and Trough (MVAT), Central Indian Ridge (CIR) and Mid-Atlantic Ridge (MAR)). Sequence typing based on 11 protein-coding genes revealed high genetic variation, including some allele types that are widespread within regions, resulting in 102 nucleotide sequence types (STs). This genetic variation was predominantly due to mutation rather than recombination. Phylogenetic analysis of the 11 concatenated genes showed a clear geographical isolation corresponding to the hydrothermal regions they originated from, suggesting limited dispersal. Genetic differentiation among Sulfurimonas populations was primarily influenced by geographical distance rather than gas composition of vent fluid or habitat, although in situ environmental conditions of each microhabitat could not be examined. Nevertheless, Sulfurimonas may possess a higher dispersal capability compared with deep-sea hydrothermal vent thermophiles. This is the first report on MLSA of deep-sea hydrothermal vent Epsilonproteobacteria, which is indicative of allopatric speciation.